(untitled) (Journal of Science and Technology Research, 2024)
Potassium bromate (KBrO3) is used as a food additive because of its high oxidizing characteristics, which have been linked to carcinogenic and mutagenic effects. The study looked into how KBrO3 exposure during gestation affected the growth, reproductive performance, and immune cells of parental mice and their F1 generation. Thirty Swiss Albino mice (Mus musculus) aged 27±3 days were collected from ICDDR’B in Dhaka, with 10 males and 20 females. When the mice reached 45 days of age, they were randomly separated into two groups, each with ten females and five males. Group A mice served as the untreated control, while group B mice were given KBrO3 at 400 mg/liter in drinking water. Body weights were obtained at 2-week intervals. The results revealed that KBrO3 reduced growth in both male and female parental mice. The KBrO3-treated group showed considerably reduced amounts of estradiol, testosterone, and T4 (P<0.01). Male mice treated with KBrO3 showed significant (P<0.05) reductions in sperm count and motility. The KBrO3-treated mice offspring weighed less and grew slowly. Neutrophil counts were somewhat higher in mice born in the KBrO3-treated group. The F1 offspring of mice in this group had decreased sperm count, motility, and testis weight (P<0.05). Testosterone and estradiol levels were lower in F1 mice born from the KBrO3 group than in F1 mice from the control group. The findings of the study suggested that KBrO3 may have multigenerational effects on growth and reproduction. However, more research on KBrO3 is required to get clear understanding of its mechanism. J. of Sci. and Tech. Res. 6(1): 109-116, 2024